Long and Active Magnetopause Reconnection X‐Lines During Changing IMF Conditions. Issue 4 (26th March 2021) - Trattner, K. J.; Fuselier, S. A.; Petrinec, S. M.; Burch, J. L.; Ergun, R.; Grimes, E. W.
Abstract: The magnetic reconnection process at the Earth's magnetopause is observed at various times and places as either anti‐parallel or component reconnection. The two scenarios are combined in a model known as the Maximum Magnetic Shear model, which predicts the location of long and continuous reconnection X‐lines across the dayside magnetopause along the ridge of maximum magnetic shear. This study investigates a Magnetospheric Multiscale Mission (MMS) magnetopause encounter where the spacecraft had repeated contact with the boundary layers for about 40 min. While in contact with the magnetopause boundary layers, the Interplanetary Magnetic Field (IMF) slowly and continuously rotated, magnetically connecting the MMS spacecraft to different sections along an extended dayside reconnection X‐line. These magnetic connection points slide along component reconnection tilted X‐lines and also connect several times to the anti‐parallel section of the magnetopause X‐line. Despite the continuously changing IMF conditions, each magnetopause boundary layer encounter shows accelerated ion beams, indicating an active reconnection X‐line at the magnetopause that covers a length of about 20 RE . Key Points: There are long continuous X‐lines across the dayside magnetopause, consisting of segments in the anti‐parallel and component reconnection regions that connect at anchor points A magnetopause X‐line remains active in response to changing solar wind conditions, for example, a slowly rotating IMF For large dipole tilts one possible scenario is that a part of a continuous X‐line consists of short X‐lines, assembled across the magnetopause in a staircase configuration